Anisotropic hydrogels formed by magnetically-oriented nanoclay suspensions for wound dressings. Issue 47 (19th November 2019) - Yook, Sungho; Shams Es-haghi, Siamak; Yildirim, Armen; Mutlu, Zeynep; Cakmak, Mukerrem
Abstract : Anisotropic hydrogels are produced, by magnetic alignment of magnetically sensitized nanoclays followed by polymerization of the hydrogel to freeze the developed oriented structure. Abstract : Anisotropic hydrogels are produced, by magnetic alignment of magnetically sensitized nanoclays followed by polymerization of the hydrogel to freeze the developed oriented structure. The anisotropy in these hydrogels is quantitatively investigated using birefringence and 2D small angle X-ray scattering (SAXS) techniques. The oriented nanoclays being intrinsically birefringent provide optical anisotropy to the hydrogel and this orientation increases with the increase of the applied magnetic field strength. Moreover, 2D SAXS patterns also confirm that the nanoclays are oriented parallel to the permanent magnetic field in the hydrogel with an orientation order parameter of up to 0.67. The field-induced birefringence and 2D SAXS orientation results exhibit a linear correlation over the range of 0 to 9 tesla (T). The resultant anisotropic hydrogels exhibit substantial swelling anisotropy, making them suitable for wound dressings where the out of plane swelling is substantially higher than in-plane swelling to minimize in-plane stress damage to the wounds during healing.